BT-1 An autopsy case of multicentric malignant glioma, H3K27M mutant. (6th December 2021) - Hayashi, Nobuhide; Enomoto, Hiroki; Kubo, Kenji; Nakanishi, Yuta; Ishii, Kenji; Kawaguchi, Takumi; Okada, Hideo; Kuwata, Toshikazu; Tsubota, Yukari; Kanemura, Yonehiro
Abstract: Introduction: In 2016, the World Health Organization (WHO) defined diffuse midline glioma, H3K27M mutant (WHO Grade 4) as a tumor with K27M mutation in histone H3.3 (H3F3A) or H3.1 (HIST1H3B/C) that develops mainly in the midline regions of the central nervous system. Here, we report a rare case of the abovementioned disease with remote multiple lesions in addition to the midline regions that was diagnosed on the initial visit. Case: The 52-year-old man, suffered from dysarthria, dysphagia, gait disturbance, and headache that gradually worsened over several months. Non-contrast-enhanced lesions were noted in the pons(swelling and involvement of the basilar artery trunk), cerebellum, thalamus, fornix, periventricular area, hippocampus, medial aspect of bilateral frontal lobes, and distally in the right frontal cortex and apical region of the left temporal lobe. The open biopsy was performed for left cerebellar surface lesion, and the pathological and genetic diagnosis was diffuse midline glioma, H3K27M mutant. Extended focal radiation at 50Gy/25fr and corpus callosal/cerebellar boost at 10Gy/5fr were performed. The lesions were markedly reduced, and neurological symptoms were also alleviated. However, 20 months after the initial visit, neurological symptoms had worsened and cerebrospinal fluid dissemination occurred, after that died at 29 months. An autopsy revealed tumor invasion mainly in the midline regions of the cerebrum and in the cerebellum, brain stem, pituitary gland, entire spinal cord, and cauda equina. Immunostaining of the distally cerebral cortex lesions showed that with a negative result for H3G34V. Discussion/Conclusion: It was suggested that caution is required for primary differential diagnosis may be presented at multiple lesions such as remote cerebral cortex of diffuse midline glioma, H3K27M-mutant.